AUTOESTIMA EN MUJERES VÍCTIMAS DE VIOLENCIA DE GÉNERO DE LA FUNDACIÓN KARINA MIRANDA DE LA CIUDAD DE QUEVEDO - ALVARADO ESPAÑA DAMARIS ANAIS (2024)
Self-esteem is a fundamental component in a person's perception and assessment of themselves, and it directly influences their emotional and mental well-being. Gender violence, understood as any act of gender-based violence that results in physical, sexual, or psychological harm or suffering for women, not only violates their fundamental human rights, but also undermines their self-confidence and ability to value themselves positively. In the case of women who are victims of gender violence, self-esteem is often severely affected due to the continuous episodes of physical, emotional, and psychological abuse they experience. Due to this situation, the objective of this research was to analyze the effects on the self-esteem of women victims of gender violence at the Karina Miranda Foundation in the city of Quevedo. To carry out the research, a methodology consisting of a documentary research was used, with a descriptive scope and a non-experimental design, with which the psychological situation faced by the sample of 80 women victims of violence at the Karina Miranda Foundation was observed, described and analyzed. To identify the level of violence to which they have been exposed, the Gender Violence Type and Phase Evaluation Scale (EETFVG) was used. Likewise, the Rosenberg Self-Esteem Scale was applied to determine the consequences that this gender violence causes on women's self-esteem.